(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
East - Latgale Region including Rezekne city and district and Ludza City and disrtict. East - Latgale region occupies 5241 km2 (about 8% o f Latvia). There are 120273 inhabitants (4,9% o f Latvia's population). Registration of waste volume in region is formal, because waste going to dumpsites as a matter of fact is not controlled exept dumpsites used by largest towns. In East - Latgale region in year 2000 was 46 dumpsites and total waste volume 64700 m3. National Municipal Solid Waste Management Strategy foreseeing establish 10-12 new solid waste landfills in Latvia. The overall strategy in searching for a location of a new landfill includes three principal aspects: 1. The environmental impact o f a landfill has to be as low as possible. 2. The waste disposal interests should not conflict with other interests. 3. The selected site should be reasonable from economic viewpoint. Taking into consideration the above aspects, the division of the land in areas suitable and non-suitable for location of a new landfill was based on the following criteria: Geological structure and hydrogeological conditions; Distance to urban areas; Location o f particularly protected nature objects; Distance to surface water bodies.